THE DESCRIPTIVE ANALYSIS OF THE STUDENTS’ ABILITY IN READING COMPREHENSION THROUGH GROUP WORK AT THE TENTH GRADE OF SMA NEGERI 1 GIDO IN 2021/2022 - Elwin Piarawan Zebua; Meilan Selfin Bu’ulolo (UNIVERSITAS PAKUAN, 2022)
Group work is one of the strategies that promotes participation and interaction among people who work together within a group. Working with other students in groups can promote a sense of belonging. Working together in groups also gives students the opportunity to learn from and teach each other. Students often learn better from each other than they do from teacher, and how teacher implemented group work through: planning, implementation, report and reflections. However, based on the observation the students were not able to find main idea, getting detail information, locating reference, making inference and finding the meaning of vocabulary in reading a text. So, the researcher conducted a research design by using descriptive qualitative method, Where the focus of the research were to analyze how the teachers implemented group work and described the students’ ability in reading comprehension of narrative text. Furthermore, the informant of the research was class X-IIS-3 in SMA Negeri 1 Gido which consisted of 15 students. The data of the research were the students’ test of narrative text and observation of English teacher. After conducting the analysis of students’ narrative text, the result showed there was 1 (6%) student who were in very good category, while2 (13%) students who were in good category. Then there were 4 (27%) students who were in adequate category, 5 (33%) students who were in less category and there were 3 (20%) students who were in fail category. Furthermore, the result of observation and showed that the student’s ability was influenced by the level of cognitive intelligence, motivation in reading, lack of vocabulary, and student’s interest. Finally, the researcher recommendations was the students’ had to learn and practice more so they were able to get a better future result in reading comprehension.